Migratory Ecology of Pseudoplatystoma fasciatum in the Amazon Basin Revealed by Otolith Microchemistry - Luciana A. Pereira; Leandro Castello; Eric Hallerman; Donald Orth; Carolina Rodrigues da Costa Doria; Edson Rubens Ferreira Rodrigues; Fabrice Duponchelle (Diversity, 2024)
Fish migrate for varied reasons, including to avoid predators and to access feeding, spawning, and nursery habitats, behaviors that enhance their survival and reproductive rates. However, the migratory ecology of many important fishes, especially those in river–floodplain ecosystems, remains poorly understood. One fish of the Amazon Basin whose migratory behavior is poorly understood is the catfish Pseudoplatystoma fasciatum. Here, we used otolith elemental microchemistry to characterize the migration ecology of P. fasciatum in the Amazon Basin. The main research questions of this study were: (1) does P. fasciatum move between waters with different Sr isotopic signatures (87Sr/86Sr) and chemical compositions? (2) What distance do they migrate? (3) Is the migration of P. fasciatum related to age? And (4) does P. fasciatum migrate mainly upstream, downstream, or in both directions? We assessed whether P. fasciatum migrates between waters with different 87Sr/86Sr values, comparing the Sr isotopic signature of otolith transects of each individual with the range of Sr isotopic signatures within the respective rivers. We found that 34% of the 71 fish analyzed migrated between rivers with different Sr isotopic signatures and 66% did not. The mean migration distance migrated was 126 km, with most specimens migrating between 72 and 237 km. Apparently, no fish of age one or age six or older migrated. All fish that migrated were between two and five years of age, with 20% of the specimens that migrated being two years old, 40% three years old, 30% four years old, and 20% five years old. Sixty-six percent of all individuals that migrated between rivers with different Sr signatures did so bidirectionally, while 33% moved unidirectionally. According to our definition of homing behavior in which fish migrated back to the same river where they were born, 41% of all fish that migrated displayed apparent homing behavior. Our findings provide insights into the migratory ecology of P. fasciatum, corroborating and refining knowledge reported in the literature. Our results on the migratory ecology of P. fasciatum have implications for sustainable fisheries conservation and management: conserving P. fasciatum requires habitat maintenance and suitable fishing practices in spawning and nursery habitats, and managers must consider large geographic areas for effective fishery management and conservation.